Prinsip-Prinsip Pembelajaran Pendidikan Agama Islam dalam Kitab ar-Rasūl al-Mu’allim wa Asālibuhu fī al-Ta’līm - Mannan, Mannan; Salabi, Agus Salim (Pascasarjana IAIN Lhokseumawe, 2024)
Ar-Rasūl al-Mu’allim wa Asālibuhu fī al-Ta’līm by Shaykh Abdul Fattah Abu Ghuddah is one of the classical references that systematically illustrates the teaching methods of Prophet Muhammad (peace be upon him). This study aims to identify and analyze the learning principles exemplified by the Prophet and to evaluate their relevance within the context of contemporary Islamic Religious Education (PAI). The research employs a descriptive qualitative approach using content analysis of the text Ar-Rasūl al-Mu’allim. Data were examined through a literature review, synthesis of Islamic educational theories, and integration of relevant previous research findings. Each learning principle was analyzed based on its pedagogical, psychological, and methodological structure. The study identifies fourteen learning principles of the Prophet Muhammad: (1) gradual approach, (2) maintaining motivation, (3) considering individual differences, (4) nurturing the soul, (5) optimizing reasoning, (6) facilitating understanding, (7) using instructional media, (8) providing rewards, (9) capturing attention, (10) offering detailed answers, (11) being active in teaching, (12) reinforcement through repetition, (13) employing various methods, and (14) contextualizing situations. These principles are grouped into four main categories: cognitive, affective, social, and methodological strategies. The findings indicate that the Prophet’s teaching methods were holistic, adaptive, and highly relevant to 21st-century learning approaches. Integrating these principles into Islamic Religious Education can enhance teaching effectiveness, depth of understanding, and character formation among learners.